YOUTHS EMPOWERMENT THROUGH THE DEVELOPMENT OF ENTREPRENEURIAL SKILLS IN BIOLOGICAL SCIENCE - Kamar, Y. M.; Kubo, B. G. (Sokoto Educational Review, 2018)
Nigeria as a nation has an earnest vision popularly called the vision 20:2020, which implies that Nigeria should be one of the world 20 largest economies by the year 2020. But no Nation can attain such greatness without the full participation of its youths. As the most energetic and contemporary set of people who have the vigor to face the challenges of this millennium, youths need to be empowered in order to be fully engaged in meaningful development ventures. One of the effective and affordable means of empowering youths is by inculcating in them, entrepreneurial skills in their various fields of educational endeavors. Biology is one of the science subjects that is rich in entrepreneurship opportunities. This paper therefore highlights the concept of entrepreneurship, entrepreneurship opportunities, problems associated with teaching of entrepreneurship education in schools, and strategies to develop entrepreneurial skills in students so that when they graduate, they are employable or self-employed or employment providers and not as employment seekers. The paper concludes that all stakeholders’ hands must be on deck to make sure youths are empowered and recommends that Government should make available in schools all equipment required for teaching of entrepreneurship and local Resource- Persons should be employed to teach entrepreneurship in schools.